The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1371/journal.pone.0042146
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Emodin against Pancreatic Cancer Depends on Its Dual Role: Promotion of Apoptosis and Suppression of Angiogenesis

Abstract: BackgroundEmodin has been showed to induce apoptosis of pancreatic cancer cells and inhibit tumor growth in our previous studies. This study was designed to investigate whether emodin could inhibit the angiogenesis of pancreatic cancer tissues and its mechanism.Methodology/Principal FindingIn accordance with our previous study, emodin inhibited pancreatic cancer cell growth, induced apoptosis, and enhanced the anti-tumor effect of gemcitabine on pancreatic caner cells in vitro and in vivo by inhibiting the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 27 publications
4
55
0
Order By: Relevance
“…Notably, emodin inhibited epithelial-mesenchymal transition, suggesting that emodin may have anticancer effects (18). Additionally, a study demonstrated that emodin enhanced anticancer effects when used in combination with gemcitabine (19). However, little is known about the effects of emodin in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, emodin inhibited epithelial-mesenchymal transition, suggesting that emodin may have anticancer effects (18). Additionally, a study demonstrated that emodin enhanced anticancer effects when used in combination with gemcitabine (19). However, little is known about the effects of emodin in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze cell invasion, the upper surface of a filter membrane in the upper compartment of a Transwell was coated with 30 µg Matrigel. Cells (1x10 5 ) suspended in 200 µl of serum-free medium were seeded onto the upper compartment of the Transwell and the lower chambers were filled with medium containing 10% FCS and various concentrations of emodin. After 24 h, the cells remaining in the upper chamber were removed and cells on the undersurface of the filters were fixed with 70% ethanol followed by staining with 0.5% Coomassie brilliant blue for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…1A), an active monomer extracted from Rheum, Polygonum, Buckthorn and Senna, has been shown to be active against pancreatic (5,6), lung (7,8), breast (9,10), liver (11), prostate (12,13), ovarian (14), cervical (15), colon (16), gallbladder (17) and human tongue cancer SCC-4 cells (18,19). Moreover, it has been reported that emodin induces apoptosis of human breast cancer MCF-7 (20) and MDA-MB-453 cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…Down regulation of VEGF-A gene expression by emodin can probably be the result of inhibitory effect of emodin on NF-KB which is required for expression of VEGF-A gene (25).…”
Section: Discussionmentioning
confidence: 99%